Immersion of sugarcane propagules in Asterarcys quadricellularis biomass extract triggers bioactive amine production and promotes sprouting rate and early seedling growth - de Lara, Gabriel Bocchetti; Mógor, Gilda; Mógor, Átila Francisco; Lima, Guiuseppina Pace Pereira [UNESP]; Amatussi, Juliana Oliveira; de Oliveira, Ricardo Augusto; Bespalhok Filho, João Carlos (Springer Nature, 2025)
The use of one-bud propagules (OBP) as a sugarcane planting technique is widespread because of logistic advantages. Propagules from different culm positions have different physiological ages, and present different sprouting and early growth rates, which is an issue for the uniformity of the stand. Therefore, this study aimed to investigate the effect of OBP immersion in a microalga biomass extract rich in L-free amino acids, looking for a natural alternative to hazardous chemical treatments to stimulate sugarcane sprouting and plant growth. Immersion of OBP for 30 min in a 2.5 g L−1 solution of the chlorophyte microalga Asterarcys quadricellularis (AQ) improved the sprouting rate of propagules from all culm positions, the effect being most evident in the medial position. Biochemical changes involving sugar levels, and especially the bioactive amines (polyamines and indoleamines), reduced putrescine content, and improved tryptophan content of OBP. Immersion in AQ also enhanced the early growth of sugarcane, with 50-day-old plants presenting gains in culm length and diameter, increments in leaf area, and fresh mass, variably depending on the OBP position. The biometrical gains also followed biochemical changes, increasing the serotonin content of leaves. The results could be related, at least in part, to the L-free amino acid content in microalga biomass, triggering the bioactive amines as key metabolites related to the microalga growth-promoting effect. This study also provides relevant information for developing a field technique to improve and unify sugarcane sprouting and initial growth in an eco-friendly way.
Keywords: Biostimulant; Chlorophyceae; Polyamines; Saccharum spp; Serotonin; Tryptamine; Tryptophan